Book review: The education of women and the vices of men: two Qajar tracts - Abedinifard, Mostafa (My University, 2014)
The translators of The Education of Women and The Vices of Men render into English, for the first time in their entirety, two important yet understudied Qajar tracts on men and women: Ta’dib al-Nesvān and Ma’āyeb al-Rejāl. The texts had been neglected for around a century before an edition of the latter and two editions of the former appeared outside Iran in 1992.1 The texts are juxtaposed in one Persian edition and in the translation under discussion here, which the translators justify by the fact that The Vices of Men is a critical response to The Education of Women.
Keywords: translations; literary criticism